CRISPR immunity relies on the consecutive binding and degradation of negatively supercoiled invader DNA by Cascade and Cas3 - Westra, Edze R. (2012)
The prokaryotic CRISPR/Cas immune system is based on genomic loci that contain incorporated sequence tags from viruses and plasmids. Using small guide RNA molecules, these sequences act as a memory to reject returning invaders. Both the Cascade ribonucleoprotein complex and the Cas3 nuclease/helicase are required for CRISPR-interference in Escherichia coli, but it is unknown how natural target DNA molecules are recognized and neutralized by their combined action. Here we show that Cascade efficiently locates target sequences in negatively supercoiled DNA, but only if these are flanked by a Protospacer Adjacent Motif (PAM). PAM recognition by Cascade exclusively involves the crRNA-complementary DNA strand. After Cascade-mediated R-loop formation, the Cse1 subunit recruits Cas3, which catalyzes nicking of target DNA through its HD-nuclease domain. The target is then progressively unwound and cleaved by the joint ATP-dependent helicase activity and Mg(2+)-dependent HD-nuclease activity of Cas3, leading to complete target DNA degradation and invader neutralization.